Effects of a Short Course of Inhaled Corticosteroids in Noneosinophilic Asthmatic Subjects - Catherine Lemière; Caroline Tremblay; Mark FitzGerald; Shawn D Aaron; Richard Leigh; Louis-Philippe Boulet; James G Martin; Parameswaran Nair; Ronald Olivenstein; Simone Chaboillez (Canadian Respiratory Journal)
BACKGROUND: Noneosinophilic asthma has been regarded as a distinct phenotype characterized by a poor response to inhaled corticosteroids (ICS).